Strategi Pembinaan Kompetensi Dai Muda pada Forum Dai dan Ustadz Muda (FODIUM) Sumatera Utara - Leli Ardiana Maibang; Hasnun Jauhari Ritonga (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to analyze the strategy for developing young preachers’ competence at the Forum Dai dan Ustadz Muda (FODIUM) of North Sumatra, focusing on planning, program implementation, and supporting and inhibiting factors. This research used a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The informants included the General Secretary of FODIUM North Sumatra, the Secretary of FODIUM Deli Serdang, and the Vice Chairperson I of FODIUM North Sumatra. Data were analyzed through data reduction, data display, and conclusion drawing, with validity strengthened through source and technique triangulation. The results indicate that competence development strategies are implemented through da’wah training, internal practice forums, Qur’anic recitation and memorization programs, and community-based da’wah activities. The strategy is flexible and adapted to regional needs; however, challenges remain in funding, facilities, and the lack of a systematic evaluation system. This study concludes that FODIUM North Sumatra’s competence development strategy contributes to improving young preachers’ rhetorical abilities, religious knowledge, and confidence, while requiring stronger managerial and evaluation mechanisms to achieve a more structured, measurable, and sustainable development process.